Development of a biological control-based integrated management of Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae) in South Africa - Scholtz, Clarke H. (University of Pretoria, 2014)
Thesis (PhD (Entomology))--University of Pretoria, 2013.